2020
DOI: 10.1007/s40617-020-00489-w
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Efficacy and Social Validity of a Culturally Adapted Training Program for Parents and Service Providers in India

Abstract: In regions such as India, where one-to-one behavior-analytic intervention is not easily accessible, parents and service providers may advocate for children with disabilities better if they have foundational training in behavioral approaches to problem behavior. The purpose of this study was to evaluate a culturally adapted training delivered in an underresourced region of India. Ten parents and professionals from Chennai completed the training, and the researchers evaluated its effects using a multiple-baselin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 55 publications
(56 reference statements)
1
6
0
Order By: Relevance
“…Eighteen studies reported on caregiver behavior other than fidelity, including treatment selection (e.g., Gabor et al, 2016), responses to hypothetical discounting scenarios (Chadwell et al, 2019), interactions with their child (that were not part of fidelity monitoring, e.g., Blackman et al, 2020), affect (e.g., Jull & Mirenda, 2011), and correct responses on knowledge assessments or other tasks (e.g., Sivaraman & Fahmie, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen studies reported on caregiver behavior other than fidelity, including treatment selection (e.g., Gabor et al, 2016), responses to hypothetical discounting scenarios (Chadwell et al, 2019), interactions with their child (that were not part of fidelity monitoring, e.g., Blackman et al, 2020), affect (e.g., Jull & Mirenda, 2011), and correct responses on knowledge assessments or other tasks (e.g., Sivaraman & Fahmie, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…a deductive approach was taken. For this study, instances of cultural adaptations were coded into surface structure features (i.e., reflecting the intervention presentation) or deep structure features (i.e., reflecting the content of the intervention) in accordance with the cultural sensitivity model (Resnicow et al, 1999). Both the surface-and deep-level categories then had subcodes that were determined by the common features of surfacelevel structural adaptations (e.g., translation of materials) and deeplevel structural adaptations (e.g., included cultural values in intervention design) that were compiled by Barrera et al (2013) from Mier et al (2010) and Kreuter and Wray (2003).…”
Section: Codingmentioning
confidence: 99%
“…Different ways of evaluating behavioural interventions have been discussed in previous studies [20]. Recent studies have discussed the importance of evaluating the cultural validity of such interventions, as well as its efficacy [21].…”
Section: Socio Economic Factors That Influence Service Deliverymentioning
confidence: 99%